Implementasi Metode Fuzzy Time Series Untuk Meramalkan Jumlah Ekspor Produk Kopi Dari Indonesia - Siti Wardah; Susanti Sundari (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
The current trade era opens up opportunities for trading Indonesian coffee in the international market. The number of future exports can be predicted by knowing past export prices. The method that can be used to predict the number of Indonesian coffee exports to various countries is the Fuzzy Time Series method. The Fuzzy Time Series method, the forecasting technique, utilizes fuzzy sets as the basis for the prediction process. In this study, the forecasting stages include defining Xmax and Xmin, determining how many and how long class intervals are, defuzzification and defining fuzzy sets, fuzzifying data on the number of coffee exports, determining fuzzy logic relationships (FLR), establishing fuzzy logical groups (FLRG) relationships, defuzzification, and perform forecasting calculations. Using the Fuzzy Time Series Method, the results of forecasting Indonesia's coffee exports for the following year are 376371.3 tons of coffee products to be exported so that exporters can see this opportunity Keywords: Coffee, export, forecasting, fuzzy time series